2000
DOI: 10.1177/107110070002100604
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the sural nerve and its relation to the Achilles Tendon

Abstract: Sural nerve injury is a complication of Achilles Tendon (TA) rupture. We dissected 30 cadaveric lower limbs to describe the course of the sural nerve in relation to the TA. At the level of insertion of the TA into the calcaneum, the sural nerve was a mean 18.8 mm from the lateral border of the TA. The proximal course of the nerve was towards the midline such that it crossed the lateral border of the TA at a mean distance of 9.8 cm from the calcaneum. The significant individual variation in the position of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
1
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(134 citation statements)
references
References 12 publications
3
120
1
10
Order By: Relevance
“…After a mean follow-up of 4.8 years, most patients had no pain, were subjectively satisfied with the outcome, and had good or excellent results according to the anklehindfoot AOFAS score. These results compare favourably with those reported with both open and percutaneous endto-end suture [1,2,3,11,16,17,19]. Nyyssonen et al [13] retrospectively compared 39 repairs and 59 augmented reconstructions and found no differences in outcome.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…After a mean follow-up of 4.8 years, most patients had no pain, were subjectively satisfied with the outcome, and had good or excellent results according to the anklehindfoot AOFAS score. These results compare favourably with those reported with both open and percutaneous endto-end suture [1,2,3,11,16,17,19]. Nyyssonen et al [13] retrospectively compared 39 repairs and 59 augmented reconstructions and found no differences in outcome.…”
Section: Discussionsupporting
confidence: 70%
“…Simple end-to-end suture is easier to perform and requires a less extensive dissection [16], but the poor quality of the tendon at the rupture site may compromise the strength of the repair. Surgical techniques have been developed to perform end-to-end suture of the Achilles tendon percutaneously [11,15,17,19], though the incidence of rerupture and sural nerve injury seems to be higher with percutaneous techniques [1,3,18]. On the contrary, augmented reconstruction provides a stronger repair that may allow a more aggressive rehabilitation program and reduce the incidence of rerupture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the risk of injury of these neurovascular structures is greater at the distal end than at the proximal end of the distal incision. In addition, previous studies found considerable variation in anatomy of the SN [21,22], and it is essential if using this surgical approach that the surgeon be cautious with the dissection to avoid injury to this nerve.…”
Section: Discussionmentioning
confidence: 99%